2019
DOI: 10.3389/fpsyt.2019.00878
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Assessment Tools for Screening Older Adults With Low Levels of Education: A Critical Review

Abstract: Introduction: Cognitive assessment of older adults who are either illiterate or with low levels of education is particularly challenging because several battery tasks require a certain educational background. Early detection of mild cognitive impairment (MCI) in the elderly using validated screening tools is of great importance since this population group could benefit from new drugs that are being investigated for the treatment of dementias. Cutoff scores for psychometric properties of cognitive tests are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 66 publications
0
40
0
1
Order By: Relevance
“…Similarly, studies using MoCA in populations of Brazilian (Apolinario et al, 2018 ), Turkish (Yancar and Öscan, 2015 ), and Chinese (Zhang et al, 2019 ) origin have reported the influence of education level on MoCA cut-off points. A systematic review on the cultural validity of MoCA (O'Driscoll and Shaikh, 2017 ) and a critical review on BCS for older adults with low levels of education (Tavares-Júnior et al, 2019 ) suggest different cut-off points of MoCA according to education level. In this sense, taking into account the high proportion of people with low education and illiteracy in Latin America (UNESCO, 2015 , 2017 ), certain MoCA tasks (drawing of the cube, denomination of dromedary and rhinoceros, and subtract backwards by seven from 100) could not be completed easily, increasing the real suspicion of cases with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies using MoCA in populations of Brazilian (Apolinario et al, 2018 ), Turkish (Yancar and Öscan, 2015 ), and Chinese (Zhang et al, 2019 ) origin have reported the influence of education level on MoCA cut-off points. A systematic review on the cultural validity of MoCA (O'Driscoll and Shaikh, 2017 ) and a critical review on BCS for older adults with low levels of education (Tavares-Júnior et al, 2019 ) suggest different cut-off points of MoCA according to education level. In this sense, taking into account the high proportion of people with low education and illiteracy in Latin America (UNESCO, 2015 , 2017 ), certain MoCA tasks (drawing of the cube, denomination of dromedary and rhinoceros, and subtract backwards by seven from 100) could not be completed easily, increasing the real suspicion of cases with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, those below 60 years of age and who are unwilling to finish the questionnaire will be excluded. A six-item screener will be used to measure the cognitive impairment of potential study participants as it is brief, reliable, and easy to administer [ 29 , 30 ]. Besides, auditory and visual assessments of the participants will also be conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Different tests have been proposed to evaluate cognitive function including memory, orientation, attention, reasoning and judgment, language skills, and attention [17,18,19]. Examples of such tools include the Eight-item Informant Interview to Differentiate Aging and Dementia (AD8), Annual Wellness Visit (AWV), General Practitioner Assessment of Cognition (GPCOG) and Health Risk Assessment (HRA), Memory Impairment Screen (MIS) (i.e., it is for testing verbal memory capability), Short Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE), Montreal Cognitive Assessment (MoCA) (i.e., it consists of a 30points scales [20] to identify subjects with MCI) [21], Addenbrooke's Cognitive Assessment (ACE) [22,23], and the Alzheimer's Disease Assessment Scale-Cognitive Subscale ADAS-Cog [24,25] (i.e., it examines attention, orientation, memory, language, visual perception, and visuospatial skills), the test can detect cognitive impairment that is related to AD and fronto-temporal dementia.…”
Section: Cognitive and Neuropsychological Assessmentsmentioning
confidence: 99%
“…Another essential attribute that might affect the fairness of ML-based LA tools is the level of education. It has been shown that some LA tools cannot provide accurate diagnostic when there are subjects with low levels of education among the population of study [19]. ML-based LA tools require a set of mechanisms to ensure that end-users trust in their performances and know how the system provides output.…”
Section: Generalization -Selecting Meaningful Featuresmentioning
confidence: 99%